PENERAPAN METODE SMALL GROUP DISCUSSION DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM: DAMPAK TERHADAP PENINGKATAN PRESTASI BELAJAR PESERTA DIDIK KELAS X SMA - Zuriati Zuriati (LP2M Universitas Sarjanawiyata Tamansiswa, 2018)
This study aims to determine how the improvement of learning achievement of students in class X.9 SMAN Negeri 10 Bandar Lampung city on learning Islamic Education (PAI) through the implementation of Small Group Discussion method. The type of research used in this research is Classroom Action Research (PTK). This research was done in three cycles. Each cycle consists of four stages, namely: planning, implementation, observation, and reflection. The results of the study showed an increase in learning achievement of learners. In the first cycle the average value obtained by learners of 62.65 with a percentage of mastery of 23.53%. On the second cycle there was an average increase of 72.94 with the percentage of mastery of 64.71%. Furthermore, in the third cycle the average value of student learning achievement again increased to 79.71 with a percentage of completeness of 91.18%. Based on this, it can be concluded that the implementation of Small Group Discussion method has an impact on the improvement of learning achievement of high school X students in Islamic Religious Education subjects.Kata kunci : Small Group Discussion, Achievement